What friends do best - Emmett, Jonathan; Reed, Nathan (London : HarperCollins Children's Books, 2005)
Winston prides himself on being a great builder, but when he embarks on a large and complicated project, he learns that it helps to have friends.
Kirkus Review.
2.0
K-3
Keywords: Buildings -- Fiction; Friendship -- Fiction; Buildings -- Fiction; Friendship -- Fiction